Early- and subsequent- response of cognitive functioning in Alzheimer's disease: Individual-participant data from five pivotal randomized clinical trials of donepezil - Levine, SZ; Goldberg, Y; Yoshida, K; Samara, M; Cipriani, A; Iwatsubo, T; Leucht, S; Furawaka, TA (Elsevier, 2022)
The association between early improvement and subsequent change in cognition is unexamined in antidementia clinical trials. We aimed to examine the consequences of early-response to antidementia medication in Alzheimer's disease. Participant-level data were analyzed from five pivotal clinical trials of donepezil for Alzheimer's disease lasting up to 24 weeks (N = 1917). Early-response was based on Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog) change scores under minus four from baseline to week six, otherwise classified non-response; then subgrouped by donepezil or placebo. The primary analysis tested the group differences in ADAS-Cog change from baseline for the interval after week six up to 24, based on a three-level mixed-effects model repeated measures (MMRM) model. Four models of increasing complexity were tested, and the most parsimonious model was examined in the primary analysis. The remaining models were tested in sensitivity analysis. In the analytic sample, 32.09% (N = 396/1234) of donepezil and 24.01% (N = 164/683) of placebo participants were classified as early responders, and 67.91% donepezil (N = 838/1234), 75.99% (N = 519/683) placebo participants were not. MMRM identified a statistically significant (P < 0.05) responder group effect. Marginal means (MM) demonstrated more improvement for the early responders (donepezil: MM = −4.13, 95% CI = -5.93, −2.32; placebo MM = 1.81, 95% CI = −4.12, 0.50), compared to non-early responders (donepezil MM = 0.05, 95% CI = -1.40, 1.51; placebo MM = 2.59, 95% CI = 0.99, 4.19). Results replicated in sensitivity analysis. Our results inform clinicians regarding the extent and consequences of early improvement in cognitive functioning and potentially contribute to treatment monitoring and the design of clinical trials for Alzheimer's disease.